APPLICABILITY OF COMPOSITE INDICES OF NUTRITIONAL STATUS IN ELDERLY HEMODIALYIS PATIENTS - Fernanda Bigogno; Juliana Rodrigues; Fernando Lamarca; Renata Fetter; Ana Lúcia Pereira; Laís Morgado (The Korean Society of Nephrology, 2012)
The composite indices of nutritional status have been largely applied to assess protein energy wasting (PEW) in hemodialysis (HD) patients, but the applicability in elderly HD patients remains unknown. We aimed to assess whether the prevalence of PEW differs depending on the composite indice applied and, to evaluate the concurrent concordance between the composite indices and objective methods of nutritional status. Sixty-four elderly HD patients (male 72%; 70±3, 4 years old) were included. The indices chosen were those validated for HD and/or with high applicability in clinical practice: 7 points subjective global assessment (7p-SGA), malnutrition inflammation score (MIS), the criteria proposed by the International Society in Renal Nutrition and Metabolism (ISRNM) and the mini-nutrition assessment (MNA). For 7p-SGA and MIS, PEW was defined as score ≤5 and > 6, respectively. The objective parameters used to evaluate the concurrent concordance were BMI, body fat % (B Fat; skinfold thicknesses), phase angle (P Angle; BIA), handgrip strength (HGS; dynamometer) and serum albumin. The prevalence of PEW and the objective methods which values differed significantly between well-nourished (WN) x PEW patients across the 4 composite indices are described below: 7p-SGA MIS IRSNM MNA PEW (%) 53% 81% 28% 20% WN x PEW WN x PEW WN x PEW WN x PEW BMI NS NS <0.05 NS B fat % <0.05 2 <0.05 1,2 <0.05 1,2 <0.05 2 P Angle NS <0.05 1 <0.05 1 NS HGS NS NS NS NS Albumin NS NS NS NS NS: not significant; 1 for male; 2 for female A large variation in the prevalence of PEW was observed among the composite indices. No composite indice agreed concurrently with all objectives methods. The IRSNM, followed by the MIS had the greater concordance with the objective methods in elderly HD patients.